Seasonal Variability of The Mixed Layer Depth in The Sulawesi Sea - Mochamad Riza Iskandar; Prima Wira Kusuma Wardhani; Toshio Suga, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The Sulawesi Sea is a semi-enclosed basin located in the Indonesian Seas and considered as the one of location in the west route of Indonesian Throughflow (ITF). There is less attention on the mixed layer depth investigation in the Sulawesi Sea. Concerning that the mixed layer plays an important role in influencing the ocean in air-sea interaction and affects biological activity, the estimation of mixed layer depth (MLD) in the Sulawesi Sea is important. Seasonal variation of the mixed layer in the Sulawesi Sea between 115°-125°E and 0°-8°N is estimated by using World Ocean Atlas 2013. Forcing elements on the mixed layer in terms of surface-forced turbulent mixing from mechanical forcing of wind stress and buoyancy forcing (from heat flux as well as freshwater flux) in the Sulawesi Sea is provided by using a reanalysis dataset. The MLD is estimated directly on grid profiles with interpolated levels based on chosen density fixed criterion of 0.03 kg.m-3 and temperature criterion of 0.5°C difference from the surface. The results show that mixed layer depth in the Sulawesi Sea varies both spatially and temporally. Generally, the deepest MLD was occurred during the southwest monsoon (JJA), and the lowest MLD was occurred during the first transition (MAM) and second transition monsoon (SON). Strengthening and weakening MLD are influenced by mechanical forcing from wind stress and buoyancy flux. In the Sulawesi Sea, the mixed layer deepening coincides with the occurrence of a maximum in wind stress, and low buoyancy flux at the surface. This condition is the opposite when mixed layer shallowing occurs.